Climate change, non‐indigenous species and shipping: assessing the risk of species introduction to a high‐Arctic archipelago. Issue 1 (12th August 2013) - Ware, Chris; Berge, Jørgen; Sundet, Jan H.; Kirkpatrick, Jamie B.; Coutts, Ashley D. M.; Jelmert, Anders; Olsen, Steffen M.; Floerl, Oliver; Wisz, Mary S.; Alsos, Inger G.; MacIsaac, Hugh
Abstract Aim Anticipated changes in the global ocean climate will affect the vulnerability of marine ecosystems to the negative effects of non‐indigenous species (NIS). In the Arctic, there is a need to better characterize present and future marine biological introduction patterns and processes. We use a vector‐based assessment to estimate changes in the vulnerability of a high‐Arctic archipelago to marine NIS introduction and establishment. Location Global, with a case study of Svalbard, Norway. Methods We base our assessment on the level of connectedness to global NIS pools through the regional shipping network and predicted changes in ocean climates. Environmental match of ports connected to Svalbard was evaluated under present and future environmental conditions (2050 and 2100 predicted under the RCP8.5 emissions scenario). Risk of NIS introduction was then estimated based on the potential for known NIS to be transported (in ballast water or as biofouling), environmental match, and a qualitative estimate of propagule pressure. Results We show that Svalbard will become increasingly vulnerable to marine NIS introduction and establishment. Over the coming century, sea surface warming at high latitudes is estimated to increase the level of environmental match to nearly one‐third of ports previously visited by vessels travelling to Svalbard in 2011 (n = 136). The shipping network will then likely connect Svalbard to a much greater pool of known NIS, under conditions more favourable for their establishment. Research and fishing vessels were estimated to pose the highest risk of NIS introduction through biofouling, while ballast water discharge is estimated to pose an increased risk by the end of the century. Main conclusions In the absence of focused preventative management, the risk of NIS introduction and establishment in Svalbard, and the wider Arctic, will increase over coming decades, prompting a need to respond in policy and action.